1986
DOI: 10.1111/j.1365-2923.1986.tb01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal educational objectives at therapeutic consultation: measures of performance, educational approach and evaluation

Abstract: The study aims at measuring doctors' performance while giving therapeutic instructions and testing the effectiveness of an educational technique for affective objectives. For this purpose doctors' performance was analysed into nine components. Twenty-five trainees in internal medicine were observed and rated regarding the nine components, while instructing 40 patients with a chronic disease. Both doctors and patients were then questioned regarding the verbal components of the doctors' performance and the answe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In the search, 15 papers 14 , 16 –29 on 14 studies were found which met the selection criteria. Descriptions of the training and evaluation methods of the studies are summarized in Tables 1a and 1b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search, 15 papers 14 , 16 –29 on 14 studies were found which met the selection criteria. Descriptions of the training and evaluation methods of the studies are summarized in Tables 1a and 1b.…”
Section: Resultsmentioning
confidence: 99%
“…It is remarkable that the training objectives are not always clearly described in the studies 14 . 19 , 20 , 25 , 27 , 28 Sometimes the objectives had to be derived from the evaluation methods and result sections.…”
Section: Resultsmentioning
confidence: 99%
“…Some assessed changes in knowledge or attitudes, while others assessed the use of skills, patient satisfaction, patient compliance, or patient distress and anxiety. [1][2][3][4][5][6][7][8][9] Specific educational methods have also been studied. Such studies found that active practice with accompanying feedback is more useful in developing these skills than other passive instructional models.…”
mentioning
confidence: 99%
“…The importance of the communication factor was evident in other studies. It has been found that doctors’ correct behaviour independently of the patients’ understanding could not guarantee patient compliance (Sideris et al . 1986).…”
Section: Discussionmentioning
confidence: 99%